TAMAN WISATA KULINER DENGAN PENDEKATAN ARSITEKTUR METAFORA DI KOTA SURAKARTA - Atikasita Armin Putri; Widi Suroto; Rachmadi Nugroho (ARSITEKTURA, 2016)
Nowadays, culinary tourism  is growing very rapidly. Eating and drinking are not only a basic need but also become one of the tourist destinations. Solo city is one of the cities that have potential in the development of culinary tourism. Solo city that has its own identity as a city of culture, has also been named as the first rank cities culinary tourism destinations in Indonesia. The government also has a plan to increase the culinary center at Solo in the year 2017-2019. The planned culinary center have to maintain a culinary hallmark of of Solo, so the plan  need methods to achieve those goals. Therefore, the approach used as a metaphor of architecture appropriate method in the design of container culinary tourism. Architectural metaphor used is combined metaphor which combination of tangible metaphor and intangible metaphor.Tangible metaphor will be applied in the form of forms that act as a culinary hallmark visualization Solo with the aim to attract visitors, while intangible metaphor will be applied as forming distinctive atmosphere is non-visual to reinforce the impression of the culinary Solo. Keywords: Culinary Tourism, Food Tourism, Intangible Metaphor Architecture, Metaphor Architecture, Tangible Metaphor Architecture